Restitution of Non-Gratuitously Conferred Benefit in Malaysia: A Case for Sowing the Unjust Enrichment Seed - SEE, Alvin W. L. (Institutional Knowledge at Singapore Management University, 2016)
This article draws on the common law of unjust enrichment to rationalize and develop the right to recover a non-gratuitously conferred benefit set out in section 71 of Malaysia’s Contracts Act 1950. This attempt at legal transplant and modern restatement is made in the hope of injecting principle and clarity into the antique section with the eventual goal of reviving it for practical and modern use.